Existence, uniqueness, and asymptotic stability for a thermoelastic plate - Amendola, G. (Нелінійні коливання, 2003)
In this note we are concerned with the linear theory of a thermoelastic plate when a rate-type equation
is assumed for the heat flux. We consider an initial boundary-value problem for this plate and show the
existence, uniqueness, and asymptotic stability of the solution. Thermodynamic restrictions on the assumed
constitutive equations are also derived. Finally, we give the expression of a pseudo free energy. Розглядається лiнiйна теорiя для термоеластичної платiвки за умови, що тепловий потiк задовольняє рiвняння швидкiсного типу. Доведено iснування, єдинiсть та асимптотичну стiйкiсть розв’язку граничної задачi з початковими умовами. Знайдено термодинамiчнi обмеження
на рiвняння задачi. Також наведено вираз для псевдовiльної енергiї.